ADAB BERBICARA DALAM AL-QUR’AN DAN IMPLEMENTASINYA DI SDIT AL BIRUNI MANDIRI JIPANG MAKASSAR - Astuti, Rati; Khalid, Muhammad Rusydi; Basri, Halimah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2020)
This writing talks about implementation of spoken moral insight in Quran at one of private school in Makassar, called SDIT Al Biruni Mandiri Jipang Makassar. In view of this era the morals of children have declined that proven by too many incidents were not supposed to happen. That happened because teaching and practicing about morals began to diminish so the student treats his teacher as he treats his friend. Consequently, in view of Quran is guidance of the mankind which talks about all of life problems in this world and here after, So, the main standard to set the concept as a rule that should be adhered to. The author is collecting information by learning quran verse was using term "qala" which has meaning the rule of speak. In this process the researcher finded nine terms, are "qaulan ma'rufa, qaulan sadidan, qaulan baligan, qaulan kariman, qaulan maisuran, qaulan layyinan, qaulan 'adziman, al-jahr bissu' dan ahsan qaulan." From this research has resulted that SDIT al-Biruni Mandiri Jipang Makassar, has taught and practiced the nine terms in school environment, but in makassar culture like iye and ki.